ANALISIS HUBUNGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF CONFIDENCE SISWA SMP - Puri Nur Aisyah; Nilam Nurani; Padillah Akbar; Anik Yuliani (Departement of Mathematics Education, 2018)
This study aims to interpret the ability to solve mathematical problems, student self-confidence, and also the relationship between the ability to solve math problems and confidence of junior high school students. This type of research is qualitative research. The subject of this research is seventh grade students in one of junior high school in West Bandung regency with a sample of 31 students. Instruments used in this research are 1) problem solving test in the form of description of 5 problem with material of rectangle and triangle; 2) self-confidence questionnaire of 30 statements. The results showed that the ability to solve medium math problems, students' self-confidence is moderate, and between the ability of problem solving and confidence of junior high school students showed a significant relationship.